Efeito da suplementação na ração de Drosophila Melanogaster (Meigem, 1830) com o fungo Pleurotus Citrinopileatus (singer, 1942) e Lentinus Sajor-Caju (fr.) Fr. e a sua relação com a reprodução de moscas das frutas. - Bolson, Sibele Marques (2016)
Effects of supplementation in the diet of Drosophila melanogaster (MEIGEM, 1830) with the fungus Pleurotus Citrinopileatus (SINGER, 1942) and Lentinus sajor-cashew (Fr.) Fr. and its relationship with the reproduction of fruit flies. The mushrooms of genus Pleurotus are widely used as food, rich in protein and antioxidants when added to animal feed increases its nutritional value. The fungi of this genus are noted for easily grow in a wide variety of substrates which facilitates cultivation and increases its biotechnological use. The species of fly, Drosophila melanogaster (Meigen, 1830) is a reference in biological and genetic studies, especially because it is easy to maintain in the laboratory and mainly have similar metabolic reactions to mammals. In nature uses as food yeasts that colonize fruits, flowers and fungi putrefying stage. This study aims to identify the effect of Pleurotus Citrinopileatus and Lentinus sajor-caju in Drosophila melanogaster body. First fungi were grown on rice straw, the fruiting bodies were weighed into 0,5-1,0-1,5-2,0-2,5-3,0 (g) were homogenized ration composed of flour maize (Klein et al, 1999) and supplied as feed for D. melanogaster, they were kept in chamber at 25 ° C ± 1. The counting larvae and pupae every twenty-four hours and the final number of flies. How to analyze the possible genotypic changes made to DNA extraction and PCR, these data were analyzed with the NTSYS 2.1 program. The results were tested for analysis of variance with the aid of Statistix8 program. It was observed that the mycelium of P. citrinopileatus stimulated reproduction in D. melanogaster, accelerating the reproductive cycle and the number of individuals compared with control and other species L. sajor-caju. The concentration of 1.5g of mycelium in the substrate was best expressed this feature and the one that showed genotypic change. The experiment suggests that the use of mycelium of P. citrinopileatus added to feed for D. melanogaster grown in the laboratory, it can be used as a reproductive stimulant for this organism, but its effect on genetic changes should be better investigated.